Numerical and Experimental Analysis of Influence of Impeller Structures on Slurry Pump Performance - Guangjie Peng (Frontiers Media S.A., 2021)
Slurry pump as an important equipment for transporting coal, which are widely used in power plants, mines and other fossil energy field. Therefore, the improvement of slurry pump performance can effectively reduce the energy loss of fossil energy industry. In this paper, a novel impeller with splitter blade structure was proposed, and the internal flow field of slurry pumps with different impeller structures was analyzed. Meanwhile, according to the shape and structure of the vortex in slurry pump, the vortex can be divided into leading edge vortex, trailing edge vortex and gap leakage vortex by employing the Q criterion, and the generation mechanism of each vortex and relationship between vortex strength and flow condition were analyzed. What is more, the entropy generation theory was employed to study the energy loss of slurry pump. The pressure distribution and wear characteristics of different impeller structures under two-phase flow conditions are studied. The result shows that the energy loss caused by entropy production in the slurry pump can be declined by employing the splitter blades, which can restrain the flow separation at the impeller outlet. Thus, the impeller with splitter blades not only can reduce the energy loss of the slurry pump, but also enhance the wear characteristics of impeller under two-phase flow conditions. Finally, the result can provide the guidelines for the design optimization of slurry pump.